Supply Chain Management Performance pada Retailer Bahan Bangunan - Sesilya Kempa; Jay Jovial Janitra (Institut Transportasi dan Logistik Trisakti, 2019)
The development of the building material industry sector is currently in line with the growth of regional infrastructure and physical facilities in Surabaya. The objective of this study is to analyze the effect of trust, commitment, information sharing and information quality on supply chain management performance of building material retailers in Surabaya. The sample studied was 134 owners of building material retailers in Surabaya. The analytical method used is multiple linear regression using SPSS 20. The results show that trust, commitment, information sharing, and information quality significantly influence partially and simultaneously on supply chain management performance of building material retailers in Surabaya.